An introduction to the Trinity - Marmion, Declan; Van Nieuwenhove, Rik, 1967- (Cambridge ; New York : Cambridge University Press, 2011)
"Over the last decade there has been a resurgence of writing on the Trinity, indicating a renewal of ideas and debate concerning this key element of Christian theology. This introduction challenges the standard account of a decline and revival in Trinitarian theology, taking into account recent, alternative readings of the theological tradition by Lewis Ayres and Michel Barnes amongst other scholars. By clearly analysing the scope of these new approaches, the authors establish the importance of a considered understanding of the Trinity, resisting the notion of separating faith and reason and identifying theology's link to spirituality. Their account also eschews the easy stereotypes of Western Christianity's supposedly more Unitarian approach as opposed to the more Trinitarian view of the East. Offering an overview of the main people and themes in Trinitarian theology past and present, this book thus provides an accessible, comprehensive guide for students and scholars alike"--Provided by publisher.
"Much current writing on the Trinity refers to a renaissance of trinitarian theology. Certainly the last two decades has seen a surge in publications on the Trinity - incorporating historical, contemporary and inter-disciplinary perspectives. It is as if theologians want to compensate for a legacy of marginalisation, particularly of pneumatology, within theology. Not that theology was ever entirely unaware of its trinitarian foundations and structure. But this framework remained to a large extent implicit, rather than explicit. The generalised and somewhat caricatured description of this state of affairs is that the doctrine of the Trinity developed in an abstract and speculative direction"--Provided by publisher.
Introducing trinitarian theology -- The Trinity and its scriptural roots -- The doctrine of the Trinity : its emergence and development in the life of the Christian community -- Theology of the Trinity from Richard of St Victor to the Reformation -- The Trinity from Schleiermacher to the end of the twentieth century -- Contemporary trinitarian theology : problems and perspectives.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Trinity -- History of doctrines; RELIGION / Christian Theology / General; Electronic books